DIAPH1 Promotes Laryngeal Squamous Cell Carcinoma Progression Through Cell Cycle Regulation - Yang, Jiechao; Huang, Qiang; Guo, Yang; Wei, Zheqiang; Zhou, Liang; Chen, Hui (Frontiers in Oncology, 2021)
The diaphanous related formin 1 (DIAPH1) protein is involved in the regulation of dynamic cytoskeleton reorganization, which is closely related to mitosis and the cell cycle. Cell cycle disorders are generally regarded as important underlying causes of many cancers. In the current study, we have revealed that DIAPH1 expression is an independent prognostic factor for overall survival in patients with laryngeal squamous cell carcinoma (LSCC) and that DIAPH1 promotes colony formation, cell proliferation, and G1/S progression in LSCC cells. Additionally, DIAPH1 promotes growth of AMC-HN-8 LSCC-derived tumors in vivo. In this study, RNA-sequencing analysis revealed that DIAPH1 knockdown led to changes in the expression of genes associated with signaling during the cell cycle. Using western blot analyses, we further demonstrated that DIAPH1 knockdown resulted in upregulation of p21Waf1/Cip1, p19Ink4d, p27Kip1, and p16Ink4a and downregulation of cyclinA2, cyclinD1, CDK2, CDK4, and CDK6. These results suggest that DIAPH1 influences the expression of genes in several signaling pathways and promotes LSCC progression by regulating the cell cycle.